Exploring sensory processing sensitivity: Relationships with mental and somatic health, interactions with positive and negative environments, and evidence for differential susceptibility - Christienne G. Damatac; Marleen J. ter Avest; Tom F. Wilderjans; Véronique De Gucht; Dion H.A. Woestenburg; Laurens Landeweerd; Tessel E. Galesloot; Linda Geerligs; Judith R. Homberg; Corina U. Greven (Current Research in Behavioral Sciences)
Environment may play a role in how the evolutionarily conserved personality trait sensory processing sensitivity (SPS) relates to health. Nevertheless, there has been no comprehensive investigation of the relationships between SPS and mental and somatic health outcomes in a large sample, while accounting for neuroticism and environmental variables. To better understand susceptibility to positive and negative environments, we systematically investigated associations between SPS and several health-related outcomes: stress-related traits, neurodevelopmental (ADHD and autistic) traits, well-being, and somatic health in 252 adults (ages 30–39 years) from a population-based sample. We then evaluated how environmental factors modify those relationships by testing SPS interactions with lifetime or current measures of positive or negative environments. Finally, we formally tested whether SPS is a factor for differential susceptibility. Notably, we found that higher SPS related to more burnout, anxiety, depression, stress, health complaints, and nonprescription medication use but not to total neurodevelopmental traits. Even after controlling for neuroticism, burnout, anxiety, and health complaints associations with SPS remained significant. We also found small to modest associations between SPS subscales and neurodevelopmental trait subscales. Of note, in unfavorable environments (threatening life events), higher SPS related to more autistic traits. In favorable environments (social support), SPS related to more life satisfaction, supporting the theory of SPS as a factor for differential susceptibility to environments. This study illustrates that SPS may be a risk factor for stress-related and somatic symptoms, independent of neuroticism. We conclude that SPS may moderate sensitivity to environments, possibly as an adaptation factor, enabling highly sensitive individuals to be more malleable to environmental influences.